0259 Chronotype and affective response to sleep restriction, sleep deprivation, and circadian misalignment. (25th May 2022) - Cox, Rebecca; Ritchie, Hannah; Sprecher, Kate; Burke, Tina; Smits, Alexandra; Knauer, Oliver; Guerin, Molly; Stothard, Ellen; Depner, Christopher; Wright, Kenneth
Abstract: Introduction: Late chronotypes have been shown to have decreased positive affect during the day and during sleep loss. Findings for negative affect are inconsistent. The present analysis examined the effect of chronotype on positive and negative affect during two sleep and circadian challenges. Methods: In both studies, chronotype was determined by habitual mid-sleep time. In Study 1, 10 healthy adults (5 early, 5 late chronotypes) completed a 10-day protocol of sleep restriction followed by total sleep deprivation. Participants maintained habitual 8h sleep schedules at home for 1 week, then completed a 2-day in-laboratory protocol: 4h of sleep restriction, followed by a 4h sleep opportunity, followed by 28h of sleep deprivation. Affect was assessed with the Positive and Negative Affect Schedule (PANAS) every hour during scheduled wakefulness. In Study 2, 14 healthy adults (7 early, 7 late chronotypes) completed a 39-day protocol of combined sleep restriction and circadian misalignment. Participants maintained habitual 8h sleep schedules at home for 2 weeks, then completed a 4-day in-laboratory protocol with the following sleep opportunities: 8h on night 1, 3h on night 2, and 3h on mornings 3 and 4. After 3 days of at-home unscheduled recovery sleep opportunities, the protocol was repeated. Affect was assessed with the PANAS every 3h during scheduled wakefulness. Data from each study were analyzed separately with mixed-model ANOVA. Results: Positive affect decreased during sleep restriction+sleep deprivation and sleep restriction+circadian misalignment (p<.05), regardless of chronotype. However, late chronotypes reported lower positive affect than early chronotypes across both sleep/circadian challenges (p<.05), and this effect was accounted for by baseline positive affect. Negative affect was not consistently impacted by sleep/circadian challenges or chronotype, with or without considering baseline negative affect. In both studies, chronotype did not interact with sleep/circadian challenges. Conclusion: These findings are consistent with prior work showing later chronotypes have lower positive affect. Chronotype and sleep loss/circadian misalignment may impact affect through independent mechanisms. Future work is needed to replicate these findings in larger samples with more extreme chronotypes. Support (If Any): Office of Naval Research MURI N00014-15-1-2809; CurAegis Technologies Inc. (formerly Torvec, Inc), NIH HL109706, NIH TR001082; Undergraduate Research Opportunities Grant University of Colorado Boulder.